Addressing challenges of an uncertain world: A CyberSystemic approach (2024)
Raúl Espejo has been President of wosc since 2017. He is also the Director of Syncho Research (uk), a member of the International Academy for Systems and Cybernetics Sciences (iascys), and a former Professor of Systems and Cybernetics at the University of Lincoln (uk) and Aston University (uk). He has been invited to deliver talks at many universities in Europe, China, and Latin America. He has co-published six books and edited seven special issues of journals, most recently in Futures. He has published over 120 papers in journals and books and organized various wosc international congresses in 2014 (Colombia), 2017 (Italy), an online event in Moscow (2020/2021), and in Oxford (2024). This same year, he was awarded the Norbert Wiener Medal by the American Society for Cybernetics.